Migraine in Adolescents and Socioeconomic Status - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2007)
The epidemiology of migraine, social causation, and patterns of medical treatment among adolescent migraineurs were studied in 120,000 households in various regions of the United States and reported from Albert Einstein College of Medicine, Bronx, NY.